2022
DOI: 10.1177/17479541221124036
|View full text |Cite
|
Sign up to set email alerts
|

The calculation of player speed from tracking data

Abstract: This short communication considers the calculation of player speed from tracking data. Whereas there are many player tracking systems, all rely on the collection of Cartesian coordinates corresponding to the players on the pitch. From these Cartesian coordinates, there are many ways that one could approximate player speed and acceleration. We introduce some simple principles from exploratory data analysis, which help yield more reliable speed calculations. The general principles are illustrated on various play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Current sprint modeling practices require continuous acceleration or velocity, or distance or time data. Acceleration values exported from GNSS manufacturer software may be derived from either embedded accelerometers or velocity and time samples (62). Velocity is estimated using 2 methods, positional differentiation (distance/ time) or Doppler shift, with the latter preferred because of superior accuracy (55).…”
Section: Discussionmentioning
confidence: 99%
“…Current sprint modeling practices require continuous acceleration or velocity, or distance or time data. Acceleration values exported from GNSS manufacturer software may be derived from either embedded accelerometers or velocity and time samples (62). Velocity is estimated using 2 methods, positional differentiation (distance/ time) or Doppler shift, with the latter preferred because of superior accuracy (55).…”
Section: Discussionmentioning
confidence: 99%
“…CSL tracking data have been used in various recent sport analytics investigations including Guan et al, 15 Wu and Swartz, 16 Epasinghege Dona and Swartz 17,18 and Wu et al 19 Using the CSL tracking data, we now consider the calculation of maximum acceleration for a particular player for a single match. The following development is based on Wu and Swartz 20 where there is an emphasis on the accuracy of calculations involving player tracking data. If (x(t), y(t)) denotes the location of a player at time t, then the player's velocity at time t in the x-coordinate direction is defined by…”
Section: Datamentioning
confidence: 99%
“…where Δ = 0.4 seconds is recommended for accuracy. 20 We measure acceleration as a scalar quantity, without a directional component. Therefore, following the above development, and using (3) and ( 4), we approximate a(t j ), the acceleration at time t j by…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to understand that a key part of the running load in football is the intensive load (acceleration and decelerations). Current optical tracking technologies are not capable of accurately determining acceleration and deceleration efforts (33), hence why they were not analysed in this study. However, research has suggested that intensive outputs may play a significant role in match play (2,34).…”
Section: Future Researchmentioning
confidence: 99%